ARE TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE ABLE TO INCREASE JOB SATISFACTION? - Rini Fatmawati; Arie Ambarwati; Teguh Setiawan Wibowo; Chairul Insani Ilham; Mohammad Sawir (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research is motivated by low job satisfaction. This study aims to determine and analyze whether transformational leadership and organizational culture can increase job satisfaction. The research method used in this research is descriptive method with a quantitative approach. The sample in this study was 100 employees using random sampling techniques. Data collection uses a questionnaire distributed to employees. The instruments used have been tested for validity and reliability. The collected data was analyzed using the classic assumption test and multiple linear regression using Excel and SPSS. The results of this study indicate that 1) Transformational leadership has a positive and significant effect on job satisfaction, 2) Organizational culture has a positive and significant effect on job satisfaction, and 3) Transformational leadership and organizational culture have a positive and significant effect on job satisfaction. The findings of this study indicate that if companies want to increase job satisfaction, companies must improve transformational leadership and organizational culture.